Test of Motor Proficiency Second Edition (BOT-2): Compatibility of the Complete and Short Form and Its Usefulness for Middle-Age School Children - Jírovec, Jan; Musálek, Martin; Mess, Filip (Frontiers in Pediatrics, 2019)
Background: The Bruininks-Oseretsky Test of Motor Proficiency Second Edition (BOT-2) assesses the psychomotor development. It is available in two forms. According to several studies the BOT-2 short form (SF) provides significantly higher results than the BOT-2 complete form (CF). This might be due to the use of an inadequate type of scores when comparing results of the SF and the CF. Objective: To verify whether the degree of psychomotor development assessed by the BOT-2 SF is comparable to the results of the BOT-2 CF in middle-age school children when using standard scores considering age and sex. Methods: The research sample consisted of n = 153 neurotypical children (n = 69 girls, n = 84 boys) from 8 to 11 years (9.53 ± 0.85). The degree of psychomotor development was determined by the standard scores of the BOT-2 CF and BOT-2 SF—both considering sex and age. The conformity in results between the CF and the SF, the sensitivity and specificity of the BOT-2 SF and the relations between the results of each sub-test within the BOT-2 CF and the BOT-2 SF were analyzed. Results: The BOT-2 SF provided a statistically significantly lower standard score x = 45.87 (±5.41) compared to the BOT-2 CF x = 47.57 (±8.29) p < 0.05 with middle effect size value, Hays ω2 = 0.09. The ROC analysis showed that the BOT-2 SF obtains sufficient sensitivity (84%) but poor specificity (42.9%) and AUC = 0.484 CI95% (0.31–0.62). Moreover, only 57% of total variance of the BOT-2 CF is explained by the relation between the results of the CF and the SF. Conclusion: The BOT-2 SF does not provide practically significant different results compared to the BOT-2 CF when using a proper scale for comparing both versions. In addition, poor specificity of the BOT-SF suggests that the BOT-2 SF might be a useful tool to reveal mainly psychomotorically delayed but not above average (psychomotorically advanced) children. Further, due to the weak portion of a shared common factor, it remains still unclear whether the BOT-2 CF and the BOT-2 SF measure the same behavioral domain.